NEEDLE STICK INJURIES AMONG NURSES IN LAHORE - JAVED, A; ANJUM, S; AMIR, Z; TASNEEM, SS; JABEEN, R (Biological and Clinical Sciences Research Journal, 2024)
Needle stick injuries (NSIs) are a significant occupational hazard for healthcare workers, particularly nurses, as they increase the risk of transmitting bloodborne pathogens such as hepatitis B (HBV), hepatitis C (HCV), and HIV. Objective: This study aimed to assess the prevalence, risk factors, and contributing practices associated with NSIs among nurses at Lahore General Hospital, Pakistan. Methods: A cross-sectional quantitative study was conducted from June to September 2024. A structured, pre-tested questionnaire was used to collect data from 257 nurses selected through non-probability consecutive sampling. Data were analyzed using SPSS version 20, employing descriptive and logistic regression analyses to identify associated factors. Results: The annual prevalence of NSIs among participants was 37.4%, with 12.1% reporting an NSI in the past month. Younger nurses (<30 years) and those with less than five years of experience were at higher risk. High-risk departments, such as ICU/OR (48.2%) and maternal units (44.4%), reported the highest incidence of NSIs. Unsafe practices, including needle recapping (73.2%) and inadequate infection control training (60.3%), were significant contributors. Nurses who received infection control training had a lower prevalence of NSIs (28.8%) compared to untrained staff (43.4%). Conclusion: The study highlights the urgent need for enhanced infection control training, implementation of universal safety protocols, and the use of safety-engineered devices to reduce NSI prevalence among nurses in Pakistan. Targeted interventions in high-risk departments and systemic improvements in workplace safety are critical to mitigating occupational risks for healthcare workers.